2015
DOI: 10.1002/lt.24137
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease after liver transplantation: When, What, and Who Is at Risk

Abstract: The evolution of metabolic and cardiovascular disease (CVD) complications after liver transplantation (LT) is poorly characterized. We aim to illustrate the prevalence of obesity and metabolic syndrome (MS), define the cumulative incidence of CVD, and characterize risk factors associated with these comorbidities after LT. A retrospective review of 455 consecutive LT recipients from 1999 to 2004 with an 8-to 12-year follow-up was performed. Obesity increased from 23.8% (4 months) to 40.8% (3 years) after LT. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
162
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 21 publications
2
162
2
3
Order By: Relevance
“…In summary, this study by Fussner et al 10 from the Mayo Clinic provides new, clinically relevant information regarding the prevalence of CVD, its impact on the short-and long-term outcome as well as potential risk factors. However, more data from larger, prospective studies are needed both to identify patients with high risk of CVD and to optimize the post-LT management in order to minimize MS and CVD and to further improve the long-term outcome of LT recipients.…”
Section: See Article On Page 889mentioning
confidence: 94%
See 1 more Smart Citation
“…In summary, this study by Fussner et al 10 from the Mayo Clinic provides new, clinically relevant information regarding the prevalence of CVD, its impact on the short-and long-term outcome as well as potential risk factors. However, more data from larger, prospective studies are needed both to identify patients with high risk of CVD and to optimize the post-LT management in order to minimize MS and CVD and to further improve the long-term outcome of LT recipients.…”
Section: See Article On Page 889mentioning
confidence: 94%
“…In the current issue of Liver Transplantation, Fussner et al 10 provide interesting data regarding the cumulative incidence of obesity, MS, and CVD and potential risk factors associated with these morbidities following LT. In this single-center, retrospective study, 455 patients were included.…”
Section: See Article On Page 889mentioning
confidence: 99%
“…305,306 A retrospective review of 455 consecutive liver transplant patients has shown that despite the exclusion of high CV risk candidates for liver transplantation, CVD occurs in 10.6% of liver transplant recipients at 1 year, 20.7% at 5 years, and 30.3% at 8 years posttransplant. 307 Fatal and nonfatal CVEs can also persist into the second decade postliver transplant. 308 …”
Section: Cvd In Kidney and Liver Transplant Recipientsmentioning
confidence: 99%
“…295 For liver transplant recipients, diabetes and hypertension are each associated with an approximate twofold higher risk of experiencing a CVE posttransplant (multivariate analysis). 288 In liver transplantation, diabetes has also been linked with long-term CVD, 307 with duration of diabetes, but not hypertension or hyperlipidemia, shown to be an independent predictor of long-term mortality due to the combination of CVE, recurrent HCV, and infection. 330 The evaluation of inflammatory markers also suggests that patients are at high cardiovascular risk after liver transplantation.…”
Section: Risk Factors For Cves In Kidney and Liver Transplant Recipientsmentioning
confidence: 99%
“…2 Whether the patients were excluded from the candidate list before LT or not, some cardiovascular risk factors could be overlooked due to end-stage liver disease. 2 Fussner et al 3 pointed out that more than 30% of their transplant recipients had a risk of cardiovascular disease, including coronary artery disease, congestive heart failure, stroke or transient ischemic attack, arrhythmias, cardiac arrest, and symptomatic peripheral vascular disease, despite the exclusion of high cardiovascular risk candidates.…”
mentioning
confidence: 99%